Optical and protective properties of different type diamond and diamond-like carbon films - Semikina, T.V.; Shmyryeva, A.N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2001)
Comparative analyses of diamond and diamond like carbon film optical properties prepared by laser and chemical vapor deposition methods are represented in this work. It was obtained that DF and DLC films have optical properties enabling to use them as antireflection coatings for solar cells. Application of both film types as protective antireflection coatings for solar cells operating under Earth conditions has enabled to increase solar cell efficiency up to 19.5 %. Solar cell degradation characteristics when using DLC coatings under space radiation conditions are represented. It was obtained that application of DLC films prepared by chemical deposition method at self-bias voltage -300 V has allowed to considerably reduce short-circuit current degradation as compared with that of another protective coatings.